PRODUCTION OF BIODIESEL FROM POULTRY WASTE - NAGARAJA Y P,; VENKATESH H S,; VINAY M S, (International Journal of Pharma and Bio Sciences, 2014)
This paper highlights the significance of biodiesel production as a sustainable potential feedstock from chicken fat by single step transesterification process. Effect of various process variables such as amount of catalyst, temperature, amount of methanol and reaction time on biodiesel production was investigated. The optimal condition for processing (66.7g) of chicken fat was obtained. Under optimal conditions, the maximum yield of (94.76%) chicken fat methyl esters was achieved by using (1:9) molar ratio of chicken fat to methanol, at temperature (35oC), for a reaction time of (45min) in the presence (1%) by weight of Potassium hydroxide(KOH) catalyst. The fuel properties like Density, kinematic viscosity, acid value, Moisture content, iodine value, saponification value, peroxide value, fire point and Flash point was estimated and was found to compare well with ASTM standards. To analyse the FAME, NMR was used and confirmed. Chicken fat was found to be highly suitable to produce biodiesel with recommended fuel properties.